An Exploratory Study of the Determinants of the Decision-Making Process of Local Government During the COVID-19 Pandemic in Indonesia - Agus Heruanto Hadna (Jurnal Politik Indonesia: Indonesian Political Science Review, 2022)
This study aims to answer how complex decision making is and what factors determine the decision making process in regions to manage the impact of the COVID-19 pandemic. This study uses the perspective of decision-making theory in crisis. However, this study is not intended to prove one specific theory. This study is an exploration type. It is intended to explore the practice of decision making in crises. The unit of analysis for this study is the highest officials, both executive and legislative, at the provincial and district levels, where it has been awarded as the best province in handling the COVID-19 pandemic. The total of respondents who completed the online questionnaire form were 45 percent of all DPRD members in the province and district; and 41 percent of provincial and district government officials. This study found new findings that executive leaders, rather than legislators, believed that pandemic-era decision-making was complex. The second new finding of this study is that the crisis has encouraged the emergence of transformational leadership. The last new finding is the consideration of the consequences of decision making that affect executive leaders in making decisions. Other factors that determine the extent of the complexity of the decision-making identified are organizational and management capacity and government innovation capacity.